The integration of Islamic deliberative values in party politics: A case study of PDI Perjuangan Deli Serdang branch - Muhammad Fachrurrozy; Hasyimsyah Nasution; Junaidi Junaidi; Nurun Nisa (Universitas Muhammadiyah Malang, 2025)
The limited involvement of local party members in political decision-making processes reflects the persistent weakness of internal democratic practices within political parties. This issue is crucial to examine as it contradicts the values of deliberation (musyawarah) upheld in Indonesia's political system and in Islamic teachings. This study focuses on the implementation of musyawarah in political decision-making within the Branch Leadership Council (DPC) of the Indonesian Democratic Party of Struggle (PDI Perjuangan) in Deli Serdang Regency. It explores its relevance to the Islamic concept of shura. Employing a qualitative approach with a phenomenological design, data were collected through in-depth interviews and direct observations of the party’s decision-making processes. The findings indicate that while musyawarah is formally practiced, it does not fully reflect the principles of shura, which emphasize equality, justice, and active participation of all members. This study offers a concrete contribution by proposing a model of political decision-making grounded in Islamic shura values to strengthen substantive democracy at the local level. Minimnya keterlibatan kader partai tingkat lokal dalam proses pengambilan keputusan politik menunjukkan masih lemahnya praktik demokrasi internal dalam partai politik. Kondisi ini penting untuk dikaji karena bertentangan dengan nilai-nilai musyawarah yang dijunjung dalam sistem politik Indonesia dan ajaran Islam. Penelitian ini berfokus pada pelaksanaan musyawarah dalam pengambilan keputusan politik di Dewan Pimpinan Cabang Partai Demokrasi Indonesia Perjuangan Kabupaten Deli Serdang, serta menelusuri relevansinya dengan prinsip syura dalam perspektif Islam. Penelitian ini menggunakan pendekatan kualitatif dengan desain fenomenologis, melalui wawancara mendalam dan observasi terhadap proses pengambilan keputusan di lingkungan partai. Hasil penelitian menunjukkan bahwa pelaksanaan musyawarah telah dilakukan secara formal, namun belum sepenuhnya mencerminkan prinsip syura yang mengedepankan kesetaraan, keadilan, dan partisipasi aktif semua anggota. Penelitian ini berkontribusi secara konkret dalam bentuk rekomendasi model pengambilan keputusan politik berbasis nilai-nilai syura Islam yang dapat memperkuat demokrasi substansial di tingkat lokal.